A fractional order model that studies terrorism and corruption codynamics as epidemic disease. (April 2023) - Baba, Isa Abdullahi; Rihan, Fathalla A.; Hincal, Evren
Abstract: Terrorism and corruption have extreme sequel towards developing economies. Many research studied terrorism, corruption and organized crime effect on macroeconomic aggregates in developing countries. Still, there is no enough literature on the coexistence of the duo. In this study, we formulate a fractional order mathematical model to study the dynamics of terrorism and corruption coexistence in communities. Existence, uniqueness and stability analysis of the solution of the model is shown. Numerical simulations are carried out to support the analytic results. Dynamics of different populations in the model is studied over a period of two years. Significance of terrorism transmission rate and corruption transmission rate in the propagation of terrorism and corruption is shown respectively. Recommendations are given to relevant stake holders for the most significant way to avert the spread of both terrorism and corruption.